Palliative care in companion animals: Review - Magalhães, Natália (Pubvet, 2021)
Palliative care is characterized by a series of patient care with no chance of cure, as in cases of terminal diagnosis or chronic disease, soothing the pain and damage caused by the disease through therapeutic measures that are selected according to the illness in question. This literature review aims to describe the criteria for palliative treatment in small animals. In situations where tutors want to prolong the life of their pet and therefore do not consider the use of euthanasia as an option, palliative care reveals its effectiveness in promoting well-being and quality of life for the patient. Palliative medicine is a valid approach as long as the condition is not a high-risk public health disease.
Keywords: Welfare; pain; palliative